PROFITABILITY DETERMINANTS OF INDONESIAN ISLAMIC BANKS: FINANCING TO DEPOSIT RATIO AND GOVERNANCE - Wahyudi, Tri; Utami, Fiesty; Sabrina, Nur (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2024)
This study aimed to thoroughly examine the impact of financing-to-deposit ratio (FDR) on profitability of Islamic commercial banks in Indonesia, with Good Corporate Governance (GCG) acting as an intervening variable. In order to achieve the objective, financial data spanning 2015 to 2019, collected from annual reports and financial statements of selected banks were analyzed. Accordingly, regression and mediation analyses were adopted to test the hypotheses. The results showed that FDR did not significantly affect profitability (measured by Return on Assets (ROA)). GCG was also observed to not efficiently mediate the relationship between FDR and ROA. These findings suggest that other factors may play a more substantial role in determining profitability of Islamic banks. The present study underscores the importance of adopting conservative financing strategies and enhancing corporate governance frameworks designed specifically in adherence to Sharia regulations. Essentially, the insights provide valuable recommendations for bank managers and policymakers to improve financial performance and ensure sustainable growth in Islamic banking sector.